INOVASI MENUJU LINGKUNGAN BERSIH DAN BERKELANJUTAN DI KOTA PONTIANAK - Romulda, Alvany; Cahyani, Elista Nanda; Safitri, Maudy; Handayani, Putri Rizki (Faculty of Social and Political Sciences, Universitas Swadaya Gunung Jati, 2023)
Waste is defined as material that is not used, sought, admired, or produced by human activity and is not clearly understood. According to the Waste Management Law Number 18 of 2008, waste is raw material originating from daily human activities and/or natural processes. One of the aims of this research is to find out how Pontianak City can produce a clean and sustainable environment. This research uses a type of library research, where data is collected through journals, books, and literature articles. The research results show that three steps can be taken by the community and government of Pontianak City to create a clean and sustainable environment: waste management, outreach and training, and substantial.